FDA regulations and prescription digital therapeutics: Evolving with the technologies they regulate - Watson, Anthony; Chapman, Richard; Shafai, Gigi; Maricich, Yuri A. (Frontiers in Digital Health, 2023)
Technological progress in digital therapeutics has outpaced the processes that the Food and Drug Administration (FDA) uses to regulate such products. Prescription digital therapeutics have entered the health care ecosystem so rapidly that some uncertainty exists about how rigorously these devices are evaluated and exactly how they are currently regulated by the FDA. This commentary briefly explains the relevant regulatory history of Software as Medical Devices and reviews the current regulatory landscape in which prescription and non-prescription digital therapeutics are approved for use.